Longitudinal Diet Studies of Arctic Whales - Matthews, Cory (Journal of the Marine Biological Association of the United Kingdom, 2013)
An animal’s foraging ecology can vary over a range of temporal scales, mirroring seasonal and longer term changes in prey availability, as well as ontogenetic shifts in diet and distribution. Obtaining individual-based, longitudinal diet information through direct observation, however, is logistically challenging for marine mammals that pursue and consume prey underwater, and are often widely distributed. Isotopic profiling along continuously growing tissues like teeth and baleen, which archive dietary inputs at the time of growth in their stable isotope composition, allows for chronological dietary reconstructions over multi-year timespans. This thesis reports longitudinal diet studies of three Arctic whale species, killer whales (Orcinus orca), bowhead whales (Balaena mysticetus) and beluga whales (Delphinapterus leucas), derived from serial isotopic measurements along teeth and baleen. Study objectives varied by species, but general goals were to characterize seasonal, ontogenetic, and/or individual diet variation. Results revealed similar trophic-level diet, but regional spatial separation, among eastern Canadian Arctic/Northwest Atlantic killer whales. However, isotope and tooth wear differences between two individuals and the rest of the sampled whales suggested potential specialisation on sharks, while the other whales likely had diets comprising marine mammals. Cyclic isotopic variation along Eastern Canada-West Greenland bowhead whale baleen was consistent with year-round foraging, although at a reduced rate during winter. Resting zooplankton could be an important food resource outside of periods of peak productivity, and accessibility likely drives winter habitat selection. Isotopic cycling did not differ between female and male bowheads, or among age classes, indicating similar seasonal foraging patterns despite reported spatial segregation throughout their summer range. Individual beluga whales from three eastern Canadian Arctic populations varied in timing of ontogenetic diet shifts (i.e. weaning ...